Study of photoluminescence properties of BaxSr1-xTiO3:Pr3+ nanoparticles prepared by sonochemical method - AZIZI (NIM 10501045), AULIA
Metal oxides are known as basic materials used in the making of ceramics. Metal oxides are also used as semiconductor in electronic industries, catalyst in petrochemical industries, a ceramic in pharmaceutical industries as well as a luminescence material in display device. One of interesting properties of perovskite is its good stability. One of the materials with perovskite structure is strontium titanate (SrTiO3 or STO). In this experiment, We will study the synthesis of BaxSr1-xTiO3 nanoparticles with the range of 0 <_ x <_ 1 using ultrasonic radiation from ultrasonic cleaning bath as a luminescence host material by the doping of rare earth materials (RE = Pr). The synthesized samples are then characterized with X-ray diffraction measurement, scaning electron microscope (SEM) and spectro flourometer. The oxides shows a cubic structure with space group PM3M for SrTiO3 and Ba0,5Sr0,5TiO3, while for BaTiO3 shows a tetragonal structure with space group P4MM. SEM measurement result shows granular morphology with homogenity distribution, while photoluminescence measurement shows photoluminescence activity at (lambda) = 610 nm for all samples. This method indicates that sonochemical method can be applied in the synthesis of other oxides.